2015
DOI: 10.1007/s12599-014-0361-1
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Line: Overcoming Knowledge Boundaries in Enterprise Transformation

Abstract: Crossing the line: overcoming knowledge boundaries in enterprise transformation Teaser Enterprise transformations are fundamental changes in an organization. To succeed, shared understanding between many diverse stakeholder groups like program managers or business managers is essential. We analyze which properties of enterprise architecture models are beneficial for creating shared understanding. We assess the differences between stakeholders through the lens of knowledge boundaries, and enterprise architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 63 publications
1
71
0
Order By: Relevance
“…Carlile, 2002;Levina & Vaast, 2005;Gasson, 2006) boundary-work (Faraj & Yan, 2009) bounded activities (Huvila, 2012) Boundary related things boundary concept (Nolin, 2009) boundary constructs (Holford, 2016) boundary negotiating artifacts (Lee, 2007) boundary organizations (Shackley & Wynne, 1996;Perkmann & Schildt, 2015) conscription devices (Henderson, 1991) Different types of boundaries tangible, intangible; imagined and 'real' boundaries (Huvila, 2012) evolutionary boundaries (Madden, 2014) knowledge boundaries (Abraham, 2015) three-dimensional (Zhang & Jacob, 2013) We found that these new concepts seem to have a tendency to focus on elucidating boundary related activities, elaborating different types of boundaries, and explicating boundary related 'things' that, according to their proposers, are complementary to and have substantial differences with the notion of BO. A common denominator of these elaborations and extensions suggests that the notion of BO has felt too rigid, unspecific or 'thingy' to describe the particularities of the specific research cases.…”
Section: Concept Referencesmentioning
confidence: 99%
“…Carlile, 2002;Levina & Vaast, 2005;Gasson, 2006) boundary-work (Faraj & Yan, 2009) bounded activities (Huvila, 2012) Boundary related things boundary concept (Nolin, 2009) boundary constructs (Holford, 2016) boundary negotiating artifacts (Lee, 2007) boundary organizations (Shackley & Wynne, 1996;Perkmann & Schildt, 2015) conscription devices (Henderson, 1991) Different types of boundaries tangible, intangible; imagined and 'real' boundaries (Huvila, 2012) evolutionary boundaries (Madden, 2014) knowledge boundaries (Abraham, 2015) three-dimensional (Zhang & Jacob, 2013) We found that these new concepts seem to have a tendency to focus on elucidating boundary related activities, elaborating different types of boundaries, and explicating boundary related 'things' that, according to their proposers, are complementary to and have substantial differences with the notion of BO. A common denominator of these elaborations and extensions suggests that the notion of BO has felt too rigid, unspecific or 'thingy' to describe the particularities of the specific research cases.…”
Section: Concept Referencesmentioning
confidence: 99%
“…For instance, the use of coherency-oriented, high complexity models should be avoided. Instead, when interacting with local business stakeholders the focus of architects should be on lightweight artifacts and local concerns ("boundary objects" [12,13]).…”
Section: Extended Abstractmentioning
confidence: 99%
“…At present, with the critical period of China's economy into the economic transformation and industrial restructuring, we clearly recognize that, implementation of enterprise transformation, accelerate industrial upgrading, the implementation of enterprise strategic transition, it is decided whether the enterprise revitalized, and achieve a major problem of regional economic revitalization [1]. At the same time, enterprise transformation is the full use of their own internal resources based on the ability of the enterprise, is to adapt to changes in the external environment, competitive advantages to maximize as the goal, the strategic behavior of economic growth mode transformation of enterprises.…”
Section: Introductionmentioning
confidence: 99%